Zinc oxide-spherical aluminum oxide composite micro powder, preparation method and application thereof, heat-conducting gasket and heat-conducting high polymer material
By forming a zinc oxide-spherical aluminum aluminum composite microfiforms caused by the surface of spherical aluminum oxide surface, the problem of low aluminum oxide thermal conductivity and poor compatibility in the existing thermal conductivity interface material, realizing high thermal conductivity and excellent Processing molding performance.
Patent Information
- Application Number
- CN202411662678.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-20
AI Technical Summary
Among the existing thermal interface materials, alumina has low thermal conductivity and poor compatibility with polymer materials, resulting in affecting the mechanical properties and processing properties of the material when added with high content.
The zinc oxide-spherical aluminum composite microfilling is used, and a densely oxide shell layer is formed on the surface of the spherical aluminum aluminum aluminum aluminum oxide surface by high temperature melting sphericalization method to form a composite microfiform with the nuclear shell structure to improve thermal conductivity and compatibility.
It achieves high thermal conductivity and good compatibility of zinc oxide-spherical alumina composite powder, and can achieve high content addition in polymer materials to improve the overall performance of thermally conductive composite materials.
Smart Images

Figure CN119350710A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal conductive fillers, and in particular to a zinc oxide-spherical aluminum oxide composite micropowder and a preparation method and application thereof, a thermal conductive gasket, and a thermal conductive polymer material. Background Art
[0002] As electronic products continue to develop in the direction of multifunctionality and miniaturization, more and more heat is generated during the use of electronic products. If the generated heat cannot be conducted out and dissipated in time, the heat accumulation will cause the temperature of electronic components to continue to rise, seriously affecting the working efficiency and service life of electronic products, and even causing safety accidents. In order to solve the problem of heat conduction in electronic products, thermal conductive interface materials are widely used between heat-generating electronic components and radiators, which can effectively improve the heat conduction efficiency and conduct the heat generated by electronic components to the radiator in time and dissipate it. At present, thermal conductive interface materials are mainly filled thermal conductive composite materials, that is, thermal conductive fillers are added to polymer materials such as rubber and plastic to obtain thermal conductive composite materials with high thermal conductivity.
[0003] The thermal conductive filler must be added to a certain proportion in the thermal conductive composite material to form an effective thermal conductive network chain, thereby obtaining high thermal conductivity. However, a high content of thermal conductive filler will have a negative impact on the mechanical properties and processing properties of the polymer material itself. Therefore, the performance of the thermal conductive filler itself will greatly affect the comprehensive performance of the thermal conductive composite material. At present, alumina is widely used in thermal conductive interface materials due to its abundant resources and low price. However, the intrinsic thermal conductivity of alumina is relatively low (about 30W / m·K), and a high filling amount is required to obtain a higher thermal conductivity. Since ordinary irregular morphology of alumina has poor compatibility with polymer materials, a large amount of addition will seriously affect the mechanical strength and processing properties of polymer materials. The thermal conductivity of zinc oxide is 60-70 W / m·K, which is more than twice that of aluminum oxide. Zinc oxide is a thixotropic filler with good compatibility with polymer materials. When added to polymer materials, it exhibits a shear-thinning state, which can effectively improve the processing and molding properties of polymer materials, especially silicone resins, when high content of thermal conductive fillers are added. However, the particle size of zinc oxide currently used is basically submicron level. Due to its small particle size and large specific surface area, zinc oxide particles are easy to agglomerate, and there is a problem of difficulty in dispersion when used alone.
[0004] Chinese patent CN118027709A discloses a method for preparing an alumina filler, wherein alumina, zinc oxide and a silane coupling agent alcohol solution are ground in a horizontal dry ball mill, so that zinc oxide is extended on the surface of quasi-spherical alumina or spherical alumina and solid-phase coated. However, in the above preparation method, the mixing of zinc oxide and alumina is a simple physical mixing, the zinc oxide coating layer in the prepared alumina filler is uneven, the binding force between the zinc oxide coating layer and the alumina is weak, and the zinc oxide coating layer is easy to fall off during high-speed stirring and mixing, which affects the thermal conductivity of the alumina filler. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a zinc oxide-spherical alumina composite micropowder and its preparation method and application, a thermal conductive gasket, and a thermal conductive polymer material. The zinc oxide-spherical alumina composite micropowder prepared by the present invention has a core-shell structure, the zinc oxide shell layer has a uniform thickness and a high bonding strength with the spherical alumina core, and the zinc oxide-spherical alumina composite micropowder has excellent thermal conductivity.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The invention provides a method for preparing zinc oxide-spherical alumina composite micropowder, comprising the following steps: mixing zinc oxide, alumina and a silane coupling agent, melting and spheroidizing, cooling and solidifying, forming a dense zinc oxide shell on the surface of the spherical alumina, and obtaining the zinc oxide-spherical alumina composite micropowder.
[0008] Preferably, the mass of the zinc oxide accounts for 5-10% of the total mass of the zinc oxide and the aluminum oxide;
[0009] The zinc oxide particle size is 0.6 to 1.5 μm;
[0010] The particle size of the aluminum oxide is 6 to 170 μm.
[0011] Preferably, the silane coupling agent includes one or more of octyltriethoxysilane, n-decyltrimethoxysilane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane and octadecyltrimethoxysilane;
[0012] The mass of the silane coupling agent accounts for 0.2-1% of the total mass of zinc oxide and aluminum oxide.
[0013] Preferably, the mixing time is 10 to 30 minutes; the mixing includes high-speed stirring mixing, and the stirring frequency of the high-speed stirring mixing is 10 to 20 Hz;
[0014] The temperature of the molten spheroidization is 2000-2300°C.
[0015] The invention provides zinc oxide-spherical aluminum oxide composite micropowder prepared by the preparation method described in the above technical scheme, which has a core-shell structure and comprises a spherical aluminum oxide core and a zinc oxide shell layer.
[0016] Preferably, the thickness of the zinc oxide shell layer is 0.6 to 1.5 μm;
[0017] The particle size of the spherical alumina core is 5 to 150 μm.
[0018] The present invention also provides the use of the zinc oxide-spherical aluminum oxide composite micropowder described in the above technical solution as a filler.
[0019] The present invention also provides a thermally conductive gasket, the preparation raw materials of which include, by mass: 100 parts of vinyl silicone oil, 5 to 15 parts of hydrogen-containing silicone oil, 0.5 to 1.5 parts of platinum catalyst, 0.05 to 0.15 parts of inhibitor, and 1000 to 3000 parts of thermally conductive filler; the thermally conductive filler includes the zinc oxide-spherical alumina composite micropowder described in the above technical scheme.
[0020] The present invention also provides a heat-conducting polymer material, and the raw materials for preparing the material include the polymer material and the zinc oxide-spherical aluminum oxide composite micropowder described in the above technical solution.
[0021] Preferably, the polymer material includes one or more of polypropylene, polyamide, polyurethane, epoxy resin and silicone rubber.
[0022] The present invention provides a method for preparing a zinc oxide-spherical alumina composite micropowder, comprising the following steps: mixing zinc oxide, alumina and a silane coupling agent, cooling and solidifying after melting and spheroidizing, forming a dense zinc oxide shell on the surface of the spherical alumina, and obtaining a zinc oxide-spherical alumina composite micropowder. The present invention adopts a high-temperature melting method to spheroidize the material particles, the zinc oxide with a lower melting point will melt first and enrich on the surface of the alumina particles, the alumina with a higher melting point continues to melt, and quickly cools and solidifies on the surface of the dense spherical alumina core to form a dense zinc oxide shell layer, the zinc oxide shell layer has a uniform thickness and the coating of the spherical alumina core is uniform, the obtained zinc oxide-spherical alumina composite micropowder with a core-shell structure has a high sphericity, the zinc oxide shell layer has a high bonding strength with the spherical alumina core, the zinc oxide shell layer is not easy to fall off, and the thermal conductivity is excellent. Moreover, the zinc oxide shell layer has good compatibility with polymer materials, is easy to achieve high-content filling in polymer materials, can solve the problem of poor filling performance of existing alumina, and effectively improves the thermal conductivity of polymer materials. Moreover, the high-temperature melting method adopted by the present invention to spheroidize the particles has simple process and convenient operation, and is suitable for industrial mass production.
[0023] The zinc oxide-spherical alumina composite micropowder prepared by the present invention has a zinc oxide shell layer tightly combined with a spherical alumina core, the zinc oxide shell layer is not easy to fall off, the zinc oxide-spherical alumina high thermal conductivity composite micropowder particles are regular spherical, and have good thermal conductivity, and the zinc oxide shell layer with a high thermal conductivity coefficient has good compatibility with polymer materials. The zinc oxide-spherical alumina composite micropowder can be added in a high content in polymer materials as a thermal conductive filler, and can be added to polymer materials such as polypropylene (PP), polyamide (PA), polyurethane (PU), epoxy resin, silicone rubber (especially addition-type liquid silicone rubber), etc., to obtain a thermal conductive composite material with high thermal conductivity and excellent processing and molding performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a SEM image of the angular alumina used in Example 2;
[0025] Figure 2 This is a SEM image of the zinc oxide-aluminum oxide mixture prepared in Example 2;
[0026] Figure 3 This is a SEM image of the zinc oxide-spherical aluminum oxide composite micropowder with a core-shell structure prepared in Example 2;
[0027] Figure 4 This is a SEM image of the polished cross section of the zinc oxide-spherical aluminum oxide composite micropowder with a core-shell structure prepared in Example 2;
[0028] Figure 5 This is a SEM image of the polished cross-section of the zinc oxide-spherical alumina composite micropowder with a core-shell structure prepared in Example 1. DETAILED DESCRIPTION
[0029] The invention provides a method for preparing zinc oxide-spherical alumina composite micropowder, comprising the following steps: mixing zinc oxide, alumina and a silane coupling agent, melting and spheroidizing, cooling and solidifying, forming a dense zinc oxide shell on the surface of the spherical alumina, and obtaining the zinc oxide-spherical alumina composite micropowder.
[0030] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.
[0031] In the present invention, the zinc oxide particle size is preferably 0.6-1.5 μm, and in specific embodiments, it can be 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm or 1.5 μm. In the present invention, the mass of the zinc oxide preferably accounts for 5-10% of the total mass of zinc oxide and aluminum oxide, and in specific embodiments, it can be 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% or 10%. The present invention can achieve precise control of the thickness of the zinc oxide shell by adjusting the ratio of zinc oxide and aluminum oxide. The present invention can achieve precise control of the particle size of the zinc oxide-spherical aluminum oxide composite micropowder by adjusting the particle size of zinc oxide and aluminum oxide.
[0032] In the present invention, the particle size of the aluminum oxide is preferably 6 to 170 μm, and in specific embodiments can be 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm or 170 μm; the aluminum oxide preferably includes angular aluminum oxide.
[0033] In the present invention, the silane coupling agent preferably includes one or more of octyltriethoxysilane, n-decyltrimethoxysilane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane and octadecyltrimethoxysilane. In the present invention, the mass of the silane coupling agent preferably accounts for 0.2-1% of the total mass of zinc oxide and aluminum oxide, and in specific embodiments, it can be 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%.
[0034] In the present invention, the mixing time is preferably 10 to 30 minutes, and in a specific embodiment it can be 10 minutes, 15 minutes, 20 minutes, 25 minutes or 30 minutes; the mixing preferably includes high-speed stirring mixing, and the stirring frequency of the high-speed stirring mixing is preferably 10 to 20 Hz, and in a specific embodiment it can be 10 Hz, 11 Hz, 12 Hz, 13 Hz, 14 Hz, 15 Hz, 16 Hz, 17 Hz, 18 Hz, 19 Hz or 20 Hz.
[0035] In the present invention, the temperature of the melt spheroidization is preferably 2000-2300°C, and in specific embodiments can be 2000°C, 2050°C, 2100°C, 2150°C, 2200°C, 2250°C or 2300°C. In the present invention, during the melt spheroidization process, the zinc oxide with a lower melting point will melt first and be enriched on the surface of the alumina particles, and the alumina with a higher melting point will continue to melt, and then the material particles will be rapidly cooled so that the particles can retain the spherical state when the particles are melted into liquid, thereby obtaining a zinc oxide-spherical alumina composite micropowder with a core-shell structure of a dense zinc oxide shell layer on the surface and a dense spherical alumina core inside.
[0036] In the present invention, the cooling and solidification method preferably includes air cooling, and the cooling rate is preferably 400-600°C / s, and in specific embodiments it can be 400°C / s, 450°C / s, 500°C / s or 550°C / s.
[0037] After the cooling and solidification is completed, the present invention preferably further comprises: screening or grading the particles obtained by cooling to obtain zinc oxide-spherical alumina composite micropowder.
[0038] The present invention also provides zinc oxide-spherical aluminum oxide composite micropowder prepared by the preparation method described in the above technical solution, which has a core-shell structure and includes a spherical aluminum oxide core and a zinc oxide shell layer.
[0039] In the present invention, the thickness of the zinc oxide shell is preferably 0.6-1.5 μm, and in specific embodiments, it can be 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm. In the present invention, the particle size of the spherical alumina core is preferably 5-150 μm, and in specific embodiments, it can be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm or 150 μm.
[0040] The present invention also provides the use of the zinc oxide-spherical aluminum oxide composite micropowder described in the above technical solution as a filler.
[0041] In the present invention, the zinc oxide-spherical alumina composite micropowder is preferably used as a filler of a polymer material, and the polymer material preferably includes one or more of polypropylene (PP), polyamide (PA), polyurethane (PU), epoxy resin and silicone rubber; the silicone rubber preferably includes addition liquid silicone rubber.
[0042] In the present invention, the addition amount of the zinc oxide-spherical aluminum oxide composite powder in the polymer material is preferably 30-97wt%, and in specific embodiments it can be 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, 90wt%, 95wt% or 97%.
[0043] The zinc oxide-spherical alumina composite micropowder prepared by the present invention has a zinc oxide shell layer tightly combined with a spherical alumina core, the zinc oxide shell layer is not easy to fall off, the zinc oxide-spherical alumina high thermal conductivity composite micropowder particles are regular spherical, and have good thermal conductivity, and the zinc oxide shell layer with a high thermal conductivity coefficient has good compatibility with polymer materials. The zinc oxide-spherical alumina composite micropowder can be added in a high content in polymer materials as a thermal conductive filler, and can be added to polymer materials such as polypropylene (PP), polyamide (PA), polyurethane (PU), epoxy resin, silicone rubber (especially addition-type liquid silicone rubber), etc., to obtain a thermal conductive composite material with high thermal conductivity and excellent processing and molding performance.
[0044] The present invention also provides a thermally conductive gasket, the preparation raw materials of which include, by mass: 100 parts of vinyl silicone oil, 5 to 15 parts of hydrogen-containing silicone oil, 0.5 to 1.5 parts of platinum catalyst, 0.05 to 0.15 parts of inhibitor, and 1000 to 3000 parts of thermally conductive filler; the thermally conductive filler includes the zinc oxide-spherical alumina composite micropowder described in the above technical scheme.
[0045] Calculated by weight, the raw materials for preparing the thermal conductive pad include 100 parts of vinyl silicone oil.
[0046] Calculated by mass percentage of the vinyl silicone oil, the raw materials for preparing the thermal conductive gasket include 5 to 15 parts of hydrogen-containing silicone oil, and in specific embodiments, it can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts or 15 parts.
[0047] The raw materials for preparing the thermally conductive gasket include 0.5 to 1.5 parts of a platinum catalyst, based on the mass fraction of the vinyl silicone oil. In specific embodiments, the raw materials may be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4 or 1.5 parts.
[0048] Calculated by mass fraction of the vinyl silicone oil, the raw materials for preparing the thermally conductive gasket include 0.05 to 0.15 parts of the inhibitor, and in specific embodiments, it can be 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14 or 0.15 parts.
[0049] Calculated by mass fraction of the vinyl silicone oil, the raw materials for preparing the thermally conductive gasket include 1000 to 3000 parts of thermally conductive filler, and in specific embodiments, it can be 1000 parts, 1500 parts, 2000 parts, 2500 parts or 3000 parts.
[0050] In the present invention, the preparation method of the thermally conductive gasket preferably comprises the following steps: mixing the raw materials, pressing and curing to obtain the thermally conductive gasket. In the present invention, the thickness of the thermally conductive gasket is preferably 0.5 to 5 mm, and in a specific embodiment, it can be 0.5 mm, 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm, 4.5 mm or 5 mm. In the present invention, the curing temperature is preferably 80 to 150 ° C, and in a specific embodiment, it can be 80 ° C, 90 ° C, 100 ° C, 110 ° C, 120 ° C, 130 ° C, 140 ° C or 150 ° C; the curing time is preferably 10 to 30 min, and in a specific embodiment, it can be 10 min, 15 min, 20 min, 25 min or 30 min.
[0051] The present invention also provides a heat-conducting polymer material, and the raw materials for preparing the material include the polymer material and the zinc oxide-spherical aluminum oxide composite micropowder described in the above technical solution.
[0052] In the present invention, the polymer material preferably includes one or more of polypropylene (PP), polyamide (PA), polyurethane (PU), epoxy resin and silicone rubber; the silicone rubber preferably includes addition type liquid silicone rubber. In the present invention, the content of zinc oxide-spherical aluminum oxide composite micropowder in the polymer material is preferably 30-97wt%, and in specific embodiments it can be 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, 90wt%, 95wt% or 97%.
[0053] The present invention has no special limitation on the preparation method of the thermal conductive polymer material, and any preparation method of thermal conductive polymer material well known to those skilled in the art may be used.
[0054] In order to further illustrate the present invention, the zinc oxide-spherical alumina composite micropowder and its preparation method and application, thermal conductive gasket, and thermal conductive polymer material provided by the present invention are described in detail below in combination with the embodiments, but they should not be understood as limiting the scope of protection of the present invention.
[0055] Example 1
[0056] S1: Put zinc oxide with a particle size of 0.6 μm and angular alumina with a particle size of 6 μm into a high-speed mixer, add octyl triethoxysilane, start the high-speed mixer, and stir and mix for 30 minutes at a stirring frequency of 20 Hz to obtain a zinc oxide-alumina mixture. The mass of zinc oxide accounts for 5% of the total mass of zinc oxide and angular alumina, and the mass of octyl triethoxysilane accounts for 0.2% of the total mass of zinc oxide and angular alumina.
[0057] S2: The zinc oxide-alumina mixture is sphericalized by high-temperature melting and then cooled and solidified to obtain a zinc oxide-spherical alumina composite micropowder with a core-shell structure. The high-temperature melting temperature is 2000°C, the thickness of the zinc oxide shell is 0.6 μm, and the particle size of the spherical alumina core is 5 μm.
[0058] S3: Classifying the zinc oxide-spherical alumina composite micropowder with a core-shell structure obtained in S2 to obtain zinc oxide-spherical alumina composite micropowder with a desired particle size distribution.
[0059] Example 2
[0060] S1: Put zinc oxide with a particle size of 1 μm and angular alumina with a particle size of 80 μm into a high-speed mixer, add dodecyl trimethoxysilane, start the high-speed mixer, and stir and mix for 20 minutes at a stirring frequency of 15 Hz to obtain a zinc oxide-alumina mixture. Among them, the mass of zinc oxide accounts for 8% of the total mass of zinc oxide and angular alumina, and the mass of dodecyl trimethoxysilane accounts for 0.3% of the total mass of zinc oxide and angular alumina.
[0061] S2: The zinc oxide-alumina mixture is sphericalized by high-temperature melting and then cooled and solidified to obtain a zinc oxide-spherical alumina composite micropowder with a core-shell structure. The high-temperature melting temperature is 2200°C, the thickness of the zinc oxide shell is 1.3 μm, and the particle size of the spherical alumina core is 70 μm.
[0062] S3: Classifying the zinc oxide-spherical alumina composite micropowder with a core-shell structure obtained in S2 to obtain zinc oxide-spherical alumina composite micropowder with a desired particle size distribution.
[0063] Example 3
[0064] S1: Put zinc oxide with a particle size of 1.5 μm and angular alumina with a particle size of 170 μm into a high-speed mixer, add hexadecyl trimethoxysilane, start the high-speed mixer, and stir and mix for 10 minutes at a stirring frequency of 10 Hz to obtain a zinc oxide-alumina mixture. The mass of zinc oxide accounts for 10% of the total mass of zinc oxide and angular alumina, and the mass of hexadecyl trimethoxysilane accounts for 0.5% of the total mass of zinc oxide and angular alumina.
[0065] S2: The zinc oxide-alumina mixture is sphericalized by high-temperature melting and then cooled and solidified to obtain a zinc oxide-spherical alumina composite micropowder with a core-shell structure. The high-temperature melting temperature is 2300°C, the thickness of the zinc oxide shell is 1.5 μm, and the particle size of the spherical alumina core is 150 μm.
[0066] S3: The zinc oxide-spherical alumina composite micropowder with a core-shell structure obtained in S2 is sieved to obtain the zinc oxide-spherical alumina composite micropowder with a desired particle size distribution.
[0067] The cross-sections of the angular alumina, the zinc oxide-alumina mixture prepared in Examples 1 to 3, the zinc oxide-spherical alumina composite micropowder with a core-shell structure, and the zinc oxide-spherical alumina high thermal conductivity composite micropowder after polishing were observed using a scanning electron microscope (SEM) for microscopic morphology.
[0068] Figure 1 This is the SEM picture of the angular alumina used in Example 2. It can be seen from the picture that the angular alumina has an irregular morphology and has many defects such as pores on the surface.
[0069] Figure 2 This is a SEM image of the zinc oxide-alumina mixture prepared in Example 2. It can be seen from the image that the small-sized zinc oxide particles are filled into the pore defects on the surface of the angular alumina, and the overall morphology of the particles is still irregular.
[0070] Figure 3 This is a SEM image of the zinc oxide-spherical aluminum oxide composite micropowder with a core-shell structure prepared in Example 2. Figure 4 This is a SEM image of the polished cross section of the zinc oxide-spherical alumina composite micropowder with a core-shell structure prepared in Example 2. Figure 5 The SEM image of the polished cross section of the zinc oxide-spherical alumina composite micropowder with a core-shell structure prepared in Example 1. It can be seen from the SEM image that the zinc oxide-spherical alumina composite micropowder with a core-shell structure prepared in the present invention has a regular morphology and a high sphericity, and the zinc oxide shell layer and the spherical alumina core are tightly combined and are not easy to fall off. In addition, the thickness of the zinc oxide shell layer can be precisely controlled by adjusting the ratio of zinc oxide and angular alumina.
[0071] Example 4
[0072] The zinc oxide-spherical alumina composite micropowder prepared in Examples 1 to 3 was used as a thermal conductive filler and was evenly mixed with vinyl silicone oil (40 cst), hydrogen-containing silicone oil, a platinum catalyst (propylene platinum trichloride) and an inhibitor (ethynyl cyclohexanol) according to the ratio in Table 1. The mixed material was processed into a sample with a thickness of 2 mm using a tablet press. The formed sample was placed in an electric heated blast drying oven and placed at 130° C. for 20 min for curing to obtain a thermal conductive pad.
[0073] Comparative Example 1
[0074] The only difference from Example 4 is that the thermal conductive filler is spherical alumina with a particle size of 150 μm, spherical alumina with a particle size of 70 μm, and spherical alumina with a particle size of 5 μm. The total amount of thermal conductive filler added is 2400 parts by mass. At this time, the rubber has good stirring performance and can be processed and formed into a thermal conductive gasket normally.
[0075] Comparative Example 2
[0076] The only difference from Example 4 is that the thermal conductive fillers are 5 μm modified aluminum oxide A prepared in Example 1 of CN118027709A, 20 μm modified aluminum oxide B prepared in Example 2 of CN118027709A, 70 μm modified aluminum oxide C prepared in Example 3 of CN118027709A, and 2 μm quasi-spherical aluminum oxide used in Example 7 of CN118027709A. The total amount of thermal conductive fillers added is 1500 parts by mass, and the rubber compound has good stirring performance at this time, and can be processed and formed into a thermal conductive gasket normally.
[0077] Comparative Example 3
[0078] The only difference from Example 4 is that the thermal conductive filler is spherical alumina with a particle size of 150 μm, spherical alumina with a particle size of 70 μm, and spherical alumina with a particle size of 5 μm. The total amount of thermal conductive filler added is 3000 parts by mass, and the mixing performance of the rubber material is extremely poor. It cannot be processed into a thermal conductive gasket.
[0079] Comparative Example 4
[0080] The only difference from Example 4 is that the thermal conductive fillers are 5 μm modified aluminum oxide A prepared in Example 1 of CN118027709A, 20 μm modified aluminum oxide B prepared in Example 2 of CN118027709A, 70 μm modified aluminum oxide C prepared in Example 3 of CN118027709A, and 2 μm quasi-spherical aluminum oxide used in Example 7 of CN118027709A. The total amount of thermal conductive fillers added is 3000 parts by mass, and the mixing performance of the rubber material is extremely poor. It cannot be processed into a thermal conductive gasket.
[0081] Referring to ASTM D5470 standard, the thermal conductivity of the thermally conductive gaskets prepared in Example 4 and Comparative Examples 1-2 was tested using a thermal conductivity tester. The results are shown in Table 1.
[0082] Table 1 Raw material ratio (mass fraction) and thermal conductivity of thermally conductive pads in Example 4 and Comparative Examples 1 to 4
[0083]
[0084]
[0085] It can be seen from Table 1 that, compared with the comparative example, the total addition amount of the zinc oxide-spherical alumina high thermal conductivity composite micropowder is significantly increased to 3000 parts by using the zinc oxide-spherical alumina composite micropowder with a core-shell structure prepared by the present invention to prepare the thermally conductive gasket, and the thermal conductivity of the thermally conductive gasket is also significantly improved to 8.47 W / m·K, which is 32.1% higher than the thermal conductivity of the gasket prepared by ordinary spherical alumina.
[0086] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing zinc oxide-spherical alumina composite micropowder, characterized in that: The following steps are involved: Zinc oxide, aluminum oxide and a silane coupling agent are mixed, melted and spheroidized, and then cooled and solidified to form a dense zinc oxide shell on the surface of the spherical aluminum oxide to obtain zinc oxide-spherical aluminum oxide composite micropowder.
2. The preparation method according to claim 1, characterized in that: The mass of the zinc oxide accounts for 5-10% of the total mass of the zinc oxide and the aluminum oxide; The zinc oxide particle size is 0.6 to 1.5 μm; The particle size of the aluminum oxide is 6 to 170 μm.
3. The preparation method according to claim 1, characterized in that: The silane coupling agent includes one or more of octyltriethoxysilane, n-decyltrimethoxysilane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane and octadecyltrimethoxysilane; The mass of the silane coupling agent accounts for 0.2-1% of the total mass of zinc oxide and aluminum oxide.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The mixing time is 10 to 30 minutes; the mixing includes high-speed stirring and mixing, and the stirring frequency of the high-speed stirring and mixing is 10 to 20 Hz; The temperature of the molten spheroidization is 2000-2300°C.
5. The zinc oxide-spherical alumina composite micropowder prepared by the preparation method according to any one of claims 1 to 4 has a core-shell structure, comprising a spherical alumina core and a zinc oxide shell.
6. The zinc oxide-spherical alumina composite micropowder according to claim 5, characterized in that: The thickness of the zinc oxide shell layer is 0.6 to 1.5 μm; The particle size of the spherical alumina core is 5 to 150 μm.
7. Use of the zinc oxide-spherical alumina composite micropowder according to claim 5 or 6 as a filler.
8. A thermally conductive pad, wherein the raw materials for preparation include, by weight: 100 parts of vinyl silicone oil, 5-15 parts of hydrogen-containing silicone oil, 0.5-1.5 parts of platinum catalyst, 0.05-0.15 parts of inhibitor, 1000-3000 parts of thermal conductive filler; the thermal conductive filler comprises the zinc oxide-spherical alumina composite micropowder according to claim 5 or 6.
9. A thermally conductive polymer material, wherein the raw materials for preparing the material include a polymer material and the zinc oxide-spherical alumina composite micropowder according to claim 5 or 6.
10. The thermally conductive polymer material according to claim 9, characterized in that: The polymer material includes one or more of polypropylene, polyamide, polyurethane, epoxy resin and silicone rubber.
Citation Information
Patent Citations
Preparation method of aluminum oxide filler and application of aluminum oxide filler in organic silicon two-component pouring sealant
CN118027709A
High-thermal-conductivity type zirconia fiber-carbon nanotube reinforced alumina-based ceramic for PCB (printed circuit board) and preparation method of alumina-based ceramic
CN107151146A
Composite heat-conducting filler, high-heat-conducting silicone grease as well as preparation method and application of high-heat-conducting silicone grease
CN116333374A
Stabilization of polymers with zinc oxide nanoparticles
US20060194910A1